Analysis of Judges' Inhibiting Factors in Deciding Criminal Cases Related to Trafficking of Women in Sexual Exploitation - Anggie Sinthiya, Ida Ayu Putu (JLASA (Journal of Law and State Administration), 2023)
In the era of globalization moment This slavery and servitude in form trading man become the more lively in its hidden and illegal form, and women are more prone to become the victim. follow criminal trafficking is all action perpetrator trafficking that contains one or more action recruitment, transportation between regional and inter- country transfers hand, departure, reception and shelter temporary or on the spot goals, women and children. As for things that are very risky moment This is follow criminal related trafficking with trading Woman to exploitation sexual. Where is trade Woman it is very damaging need base somebody for grow in safe, and destructive environment right for free from violence and exploitation sexual. And of course matter This it is very clear, that crime trafficking related with trading Woman to exploitation sexual has violate right universal human rights For alive, independent, and free from all form slavery.